Bokeljski patriciji u mletačkoj vojnoj službi - Čoralić, Lovorka (Acta Histriae, 2008)
In the past numerous patricians from the Boka Kotorska area were honoured with appointments as chevaliers of St. Mark. Therefore, the knowledge of the only Venetian chivalrous order, its structure and membership, represents a significant component in the research into the social and military history of the Boka Kotorska area under Venetian rule. Most commonly, historiographical data on Boka Kotorska chevaliers can be found within research of separate constituents of the history of Boka Kotorska, military events in the broader area of the eastern Adriatic coast in the early modern age period (mostly into Venetian-Turkish wars), or biographical data of men coming from the area who excelled militarily. Boka Kotorska men, similarly to numerous others who fought for St. Mark's Republic, would most often be appointed chevaliers for their military merits and distinguished participation in a series of Venetian wars on Adriatic and Levantine battlefields. The article analyses the documents used to grant the title of Venetian chevalier to descendants of renowned Boka Kotorska patrician families of Bolica, Paskvali, and Pima. All documents are dated within the 17th century and represent a valuable testimony of the history of these patrician families as well as the broader social and military history of the eastern Adriatic, specifically the Boka Kotorska area.
Keywords: Beneška republika; Boka Kotorska; socialna zgodovina; vitezi sv. Marka; vojna zgodovina; zgodnji novi vek